Japan shellfish farmer perceptions of ocean acidification, adaptive strategies and comparison with global shellfish farmers - Pang, Yumeng; Green, Kristen Marie; Kim, Yulan; Hamanoue, Ryuji; Furukawa, Keita; Tanaka, Takehiro; Ota, Yoshitaka (Frontiers in Marine Science, 2025)
Ocean acidification (OA) poses significant threats to shellfish aquaculture. Although governments and organizations around the globe are taking actions to mitigate the impacts of OA, few studies directly report shellfish farmer perceptions of OA and corresponding responses. In this study, we document Japanese shellfish (oyster) commercial farmer perceptions of, and adaptive strategies for OA with respect to oyster aquaculture. We also review and compare our results with existing studies of shellfish commercial farmer perceptions of OA in three regions, including the United States (U.S.), the Mediterranean region and British Columbia, Canada. We found variation in the perceptions of OA around the globe; it is common among all shellfish farmers to have difficulty distinguishing OA from other environmental stressors. OA adaptive strategies from shellfish farmers were only reported for the U.S. (in the literature), and Japan (this study). Acknowledging the diverse geographical and cultural backgrounds, we discussed the similarity and difference of adaptive strategies between the U.S. (as a post-event case with documented OA-related shellfish mortality) and Japan (as a pre-event case) to cope with OA. For example, farmers from both countries suggest, or are already utilizing flexibility in farm management and applying knowledge through hands-on learning. While U.S. farmers rely on networking with different stakeholders to learn about OA knowledge and solutions while Japanese farmers do not. Learning from the strategies that U.S. farmers applied to adapt to OA events, several areas of policies and actions (e.g., financial support, collaboration with scientists and OA awareness enhancement) were identified to better support and empower Japanese shellfish farmers to adapt to future OA scenarios. However, future study on suitability and transferability of implementing policies and actions in Japan is required due to different geographical and cultural contexts.